Adding Interpersonal Learning and Tacit Knowledge to March's Exploration-Exploitation Model - Miller, Kent D.; Zhao, Meng; Calantone, Roger J. (Academy of Management Journal, 2006)
In his classic article on exploration and exploitation, March (1991) presented an agent-based model simulating learning within an organization. His model includes mutual learning between individuals and an organizational code. We extend March's model by (1) allowing for direct interpersonal learning, (2) locating individuals in a space, which makes the distinction between local and distant search relevant, and (3) recognizing that knowledge has a tacit dimension that cannot be transmitted through codification. We also consider the implications of personnel turnover for learning over time. Our results qualify and extend March's (1991) conclusions.